Gastroprotective evaluation of Medicago sativa L. (Fabaceae) on diabetic rats - Phool Chandra; Mohammad Kaleem; Neetu Sachan; Rashmi Pathak; Ashwag S. Alanazi; Nawaf A. Alsaif; Sary Alsanea; Bader Alsuwayt; Mohammed M. Alanazi; Atul Kabra (Elsevier, 2023)
Traditional uses for the plant Medicago sativa (M. sativa) (Alfalfa) (Family: Fabaceae) include liver protection, antioxidant activity, and the treatment of bleeding and digestive issues. This study aims to assess the effect of ethanol extract of M. sativa (EEMS) on experimental-induced ulcers in diabetic rats. By pylorus ligation and ethanol administration, gastric ulcers were induced in diabetic rats. Five groups each consisting of six rats in each model were used. All other groups except Group I were made diabetic by giving rats alloxan (140 mg/kg i.p.). Vehicles were given to Group I (normal control) and Group II (diabetes control) rats. Group III (positive control) received ranitidine 50 mg/kg, and Group IV and V received EEMS at doses of 100 and 400 mg/kg, respectively. In the pylorus ligation and ethanol-induced stomach ulcer model of rats, the findings demonstrated that EEMS (100 mg/kg) showed a decreased ulcer index of 2.01 ± 0.41 and was found statistically significant against the diabetes control group (p < 0.001) as well as, an ulcer index of 0.68 ± 0.22 by EEMS (400 mg/kg) with a significant reduction in the ulcer index (p < 0.001). EEMS (100 and 400 mg/kg) reduce free acidity by 13.16 ± 0.65 mEq/L and 9.83 ± 0.30 mEq/L, respectively. EEMS also showed a protective impact on the liver and kidneys of diabetic rats. Antihyperglycemic action was also discovered in diabetic animals. The findings of the current investigation demonstrated that ethanolic extract of M. sativa possesses anti-ulcer activity in diabetic rats. Ethanolic extract of M. sativa may be a treatment option for stomach ulcers that also have diabetes.